65.6k views
2 votes
Given: F(x) = 2x - 1; G(x) = 3x + 2; H(x) = x 2 Find F{G[H(2)]}.

User Edi Wang
by
5.2k points

1 Answer

2 votes

Answer:

27

Explanation:

Evaluate from the inside out, that is

Evaluate h(2) , then use the value obtained to evaluate g(x) and the value obtained here to evaluate f(x) , that is

h(2) = 2² = 4 , then

g(4) = 3(4) + 2 = 12 + 2 = 14, then

f(14) = 2(14) - 1 = 28 - 1 = 27

User I See Voices
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.